The association between body mass index class and coronavirus disease 2019 outcomes - Al-Salameh, Abdallah; Lanoix, Jean-Philippe; Bennis, Youssef; Andrejak, Claire; Brochot, Etienne; Deschasse, Guillaume; Dupont, Hervé; Goeb, Vincent; Jaureguy, Maité; Lion, Sylvie; Maizel, Julien; Moyet, Julien; et al. (International Journal of Obesity, 2021)
Background/Objectives A growing body of data suggests that obesity influences coronavirus disease 2019 (COVID-19). Our study’s primary objective was to assess the association between body mass index (BMI) categories and critical forms of COVID-19. Subjects/Methods Data on consecutive adult patients hospitalized with laboratory-confirmed COVID-19 at Amiens University Hospital (Amiens, France) were extracted retrospectively. The association between BMI categories and the composite primary endpoint (admission to the intensive care unit or death) was probed in a logistic regression analysis. Results In total, 433 patients were included, and BMI data were available for 329: 20 were underweight (6.1%), 95 have a normal weight (28.9%), 90 were overweight (27.4%), and 124 were obese (37.7%). The BMI category was associated with the primary endpoint in the fully adjusted model; the odds ratio (OR) [95% confidence interval (CI)] for overweight and obesity were respectively 1.58 [0.77–3.24] and 2.58 [1.28–5.31]. The ORs [95% CI] for ICU admission were similar for overweight (3.16 [1.29–8.06]) and obesity (3.05 [1.25–7.82]) in the fully adjusted model. The unadjusted ORs for death were similar in all BMI categories while obesity only was associated with higher risk after adjustment. Conclusions Our results suggest that overweight (and not only obesity) is associated with ICU admission, but overweight is not associated with death.